Morphometric Analysis of the Mandibular Foramen from Different Bony Landmarks in Dry Human Mandibles - Suman Kumari; Rajendra Prasad (Academia Anatomica International, 2020)
Introduction:Mandibular foramen is an irregular foramen located just above the center of the medial surface of the ramus of the mandible leading to mandibular canal through which inferior alveolar nerve and vessels will transmits. Aim: The aim of the study was to find exact location of mandibular foramen from different anatomical landmark.Subjects and Methods:The present study evaluated 60 dry human mandibles & all the distances were measured from center of mandible to different landmark on both sides.Results:The mean of MF-AB distance on right side is 15.6mm & on left side is 15.3mm. Mean of MF-PB distance are 12.0mm & 11.0mm on right side and left side respectively. MF-MB distance 23.4 mm and 22.9 mm are the mean of MF-MN on right and left side respectively. The mean of MF-AG is 23.2mm on right side & 24.2mm on left side.Conclusion:There is great variation found in the position of MF in previous studies. The present study helps in dental anaesthesia and also would help dental surgeons to avoid complications.